2020
DOI: 10.1038/s41392-020-00326-0
|View full text |Cite
|
Sign up to set email alerts
|

NADPH homeostasis in cancer: functions, mechanisms and therapeutic implications

Abstract: Nicotinamide adenine dinucleotide phosphate (NADPH) is an essential electron donor in all organisms, and provides the reducing power for anabolic reactions and redox balance. NADPH homeostasis is regulated by varied signaling pathways and several metabolic enzymes that undergo adaptive alteration in cancer cells. The metabolic reprogramming of NADPH renders cancer cells both highly dependent on this metabolic network for antioxidant capacity and more susceptible to oxidative stress. Modulating the unique NADPH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
196
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(251 citation statements)
references
References 191 publications
(296 reference statements)
3
196
1
Order By: Relevance
“…NADPH, as the primary hydrogen donor and component of the reducing equivalent pool, maintains moderate disulfide reduction of most proteins through NADPH-dependent TRXR and GR redox systems 80 . Maintaining the dynamic equilibrium of the compartmentalized NADP+/NADPH pools is essential for cellular redox homeostasis and modulation of thiol-disulfide transformation signaling 81 .…”
Section: Antioxidant Defense Mechanismsmentioning
confidence: 99%
“…NADPH, as the primary hydrogen donor and component of the reducing equivalent pool, maintains moderate disulfide reduction of most proteins through NADPH-dependent TRXR and GR redox systems 80 . Maintaining the dynamic equilibrium of the compartmentalized NADP+/NADPH pools is essential for cellular redox homeostasis and modulation of thiol-disulfide transformation signaling 81 .…”
Section: Antioxidant Defense Mechanismsmentioning
confidence: 99%
“…It was reported that a crucial function of FAO is generating the reducing equivalent NADPH to maintain antioxidant balance. Under stress conditions, cancer cells sustain NADPH levels by increasing FAO and the concomitant downregulation of fatty acid de novo biosynthesis [ 78 ]. Pharmacological inhibition of FAO with the CPT-1 inhibitor, etomoxir, diminishes NADPH levels and glutathione content leading to an elevation of intracellular ROS [ 79 ].…”
Section: Changes In Lipid Metabolism Contribute To Anticancer Drugmentioning
confidence: 99%
“…After 7 days, GR activity in the intestine decreased in TiO 2 NPs (vs. all the treatments), suggesting impairment of NADPH homeostasis, since GR is an NADPH-dependent oxireductase, and the vulnerability of fish exposed to this NPs towards oxidative stress processes. NADPH is a reducing agent that is critical for an effective antioxidant response [ 57 ]. Data from the literature indicate that the fish intestine is prone to generate reactive oxygen species (ROS) due to its high content in polyunsaturated fatty acids [ 58 ].…”
Section: Discussionmentioning
confidence: 99%